Lamotrigine use in pregnancy and risk of orofacial cleft and other congenital anomalies. (3rd May 2016) - Dolk, Helen; Wang, Hao; Loane, Maria; Morris, Joan; Garne, Ester; Addor, Marie-Claude; Arriola, Larraitz; Bakker, Marian; Barisic, Ingeborg; Doray, Berenice; Gatt, Miriam; Kallen, Karin; et al.
Abstract : Objective: To test previous signals of a risk of orofacial cleft (OC) and clubfoot with exposure to the antiepileptic lamotrigine, and to investigate risk of other congenital anomalies (CA). Methods: This was a population-based case–malformed control study based on 21 EUROCAT CA registries covering 10.1 million births (1995–2011), including births to 2005 in which the clubfoot signal was generated and a subsequent independent study population of 6.3 million births. A total of 226, 806 babies with CA included livebirths, stillbirths, and terminations of pregnancy following prenatal diagnosis. First-trimester lamotrigine monotherapy exposure in OC cases and clubfoot cases was compared to other nonchromosomal CA (controls). Odds ratios (OR) were adjusted for registry. An exploratory analysis compared the proportion of each standard EUROCAT CA subgroup among all babies with nonchromosomal CA exposed to lamotrigine monotherapy with non-AED exposed pregnancies. Results: There were 147 lamotrigine monotherapy-exposed babies with nonchromosomal CA. For all OC, ORadj was 1.31 (95% confidence interval [CI] 0.73–2.33), isolated OC 1.45 (95% CI 0.80–2.63), isolated cleft palate 1.69 (95% CI 0.69–4.15). Overall ORadj for clubfoot was 1.83 (95% CI 1.01–3.31) and 1.43 (95% CI 0.66–3.08) in the independent study population. No other specific CA were significantly associated with lamotrigine monotherapy. Conclusions: The risk of OC was not significantly raised and we estimate the excess risk of OC to be less than 1 in every 550 exposed babies. We have not found strong independent evidence of a risk of clubfoot subsequent to our original signal. Our study cannot assess the general malformation risk among lamotrigine-exposed pregnancies.